The Teacher Training System in Andalusia: „A képzett pedagógus kulcsszereplője a társadalomnak” (Training and Practice : Journal of Educational Sciences, 2010)
The author of the paper took part in a study visit on ‘Continuous Teacher’s Training: Towards Teaching Quality Improvement’ in Seville, Spain supported by Tempus Foundation Budapest and the European Union. Educational specialists from ten different European countries studied the teacher training and the educational system in Andalusia. The organizer was the ‘Centro del Profesorado de Castilleja de la Cuesta (CEP ) near Seville; the centre has been managing and controlling the continuous teacher training for twenty years. An important aim of the study visit group was to share the nature of in-service teacher development or as some countries understand it, continued professional development. It resulted in a good discussion over and above the formal parts ofthe programme around the nature of teacher learning and whether this should rely on the concept of learning as transmission of knowledge. In this context meeting with the local Andalusian education authority was particularly illuminating as the approach taken in the region is to move teachers ’professional development from a traditional course based approach to one that encourages collaboration and the development of communities of practice. The participants agreed that well-trained teachers play key role in society.